Advancing voltage control in DC microgrids: a comparative study with IGWO-based H∞ control - Kavousighahfarokhi, Arash; Mohd Radzi, Mohd Amran; Noorbakhsh, S. Mohammad; Khorshidi, Elahe; Hematzadeh Dastgerdi, Pedram; Karimi, Mojtaba; Torki Harchegani, Amir (Springer Science and Business Media Deutschland GmbH, 2024)
DC microgrids (DC-MGs) are gaining popularity over AC microgrids (AC-MG) due to their inherent advantages, such as a greater adaptability in algorithmic control, and the absence of reactive power-related issues. However, nonlinear loads, like constant power loads (CPLs), can cause instability in DC-MGs and result in a voltage drop in the primary DC bus. This paper proposes the utilization of an Improved gray Wolf Optimization (IGWO) algorithm-based H-infinity (H∞) control approach to enhance traditional droop control techniques and address instability concerns. In this study, the presented approach is applied to optimize the effectiveness of the voltage control while improving the power quality of autonomous DC-MG. The H∞ controller's weighted parameters are precisely determined using the IGWO algorithm to enhance system stability. The stability of the controller in mitigating external disturbances is evaluated through the root locus, bode plot, and the maximum singular value plot, while the robustness of the controller is examined under two scenarios, including load and radiation changes, within the MATLAB/Simulink 2021b environment. Moreover, the proposed control strategy's performance is compared with five conventional techniques, demonstrating its superiority in terms of faster settling times and enhanced precision in managing overvoltage for the DC bus voltage. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.